Cultural variations in perceptions and reactions to social norm transgressions: a comparative study - Chen-Xia, Xing J.; Betancor, Verónica; Rodríguez-Gómez, Laura; Rodríguez-Pérez, Armando (Frontiers in Psychology, 2023)
Humans are similar but behave differently, and one main reason is the culture in which they are born and raised. The purpose of this research is to examine how the perception and reaction to those who transgress social norms may vary based on the individualism/collectivism of their culture. A study (N = 398) conducted in the United Kingdom, Spain, and China showed differences in the perception and reaction to incivilities based on individualism/collectivism. People from highly collective countries (China) perceive uncivil transgressors as immoral and enact more social control over them than people from highly individualistic countries (U.K.). They also experience more discomfort when facing uncivil transgressors, and this discomfort mediates the increasing immorality perceived on the agents of incivilities in contrast with people from less collective countries. Our findings provide insights into how cultural factors shape individuals' perceptions of social norm violations and emphasize the importance of considering cultural differences when addressing incivility. Eliminado: Rude Con formato: Inglés (americano) Eliminado: , Ruder and Rudest: A Cross-Cultural Study of Social Norms in Collectivist and Individualist Cultures Con formato: Inglés (americano) Código de campo cambiado Con formato: Inglés (americano) Con formato: Inglés (americano) Eliminado: dehumanization 40 Con formato: Inglés (americano) Con formato: Inglés (americano) Eliminado: 1.